Freiberg's infraction: A modified closing wedge osteotomy for an undiagnosed case. (2017) - Biz, Carlo; Zornetta, Alessandro; Fantoni, Ilaria; Crimì, Alberto; Bordignon, Enrico; Ruggieri, P.
Highlights: The pathogenesis of Freiberg's infraction is not fully understood. We present a 31-year old woman with an undiagnosed Freiberg's disease. Symptoms are not clearly correlated with Freiberg's infraction in its early stages; this can lead to wrong diagnosis and treatment. Dorsal closing-wedge osteotomy with single screw stabilization can be a valuable tool when conservative treatments fail. Abstract: Introduction: Freiberg's infraction is an osteonecrosis affecting the metatarsal head whose pathogenesis is not fully understood, although stress overloading by multiple microtraumas remains the most widely accepted cause. Operative treatment, by different techniques, is necessary when conservative treatment fails. Presentation of case: A 31-year old woman presented with left foot severe pain, especially at the level of the metatarsophalangeal joint (MTPJ) of the second ray, underestimated upon initial evaluation. She had a history of repetitive microtraumas, a long second metatarsal bone and altered forefoot kinematics. Clinical and radiographic findings were compatible with Freiberg's infraction. A dorsal closing-wedge osteotomy with single screw stabilization was performed. At last follow-up, the patient was completely asymptomatic with a normal MTPJ range of motion. Discussion: Our patient had a history of repetitive microtraumas combined with a long second metatarsal bone and altered forefoot kinematics. Initially, because of the low frequency of the disease and lack of knowledge about it, even among general orthopaedic surgeons, the infraction was not diagnosed. However, the radiological characteristics of the lesion, combined with intra-operative observation and histological exams associated with the medical history and clinical exam of the patient, revealed a disease compatible with Freiberg's syndrome. A closing-wedge osteotomy, performed by using a straight burr, appeared to be the most correct treatment. Conclusion: This case shows how Freiberg's infraction can pass unrecognized or underestimated and how dorsal closing-wedge osteotomy can be an efficient surgical treatment.